OPTIMALISASI PENYIMPANAN DI PT. XYZ MELALUI CLASS BLASED STORAGE DAN KLASIFIKASI ABC - Setiawan, Anggie Eka; Nuruddin, Mochammad (Universitas Bina Taruna Gorontalo, 2024)
Abstract: Storage Optimization at PT. XYZ Through Class Blased Storage and ABC Classification. This research aims to make the process of picking up goods according to their type easier, so that the distance to transport materials is shorter than before. In addition, this placement allows each type of item to be stored in the spare parts warehouse, so that when it is picked up, the item can be fully used. This research collects data through observation, support and interviews. The results of blased class storage place items in groups according to their category type. Goods with fast movement, for example, are placed closer to the exit, and goods with slow movement, for example, are placed further to the entrance. workers during the material movement process. The results of the ABC classification are 19 types of goods in category A, 3 types of goods in category B, and 1 type of goods in category C. The ABC category is created by sorting all the frequencies of goods from the highest value, as well as calculating cumulative and frequency percentages. By comparing the initial layout with the proposed layout, data processing resulted in a total reduction of Rp. 6,733,000/month to Rp. 3,738,000/month. Therefore, it can be concluded that the problem of storing goods in the PT warehouse. XYZ can be solved using a storage optimization policy that uses the class blased storage method and ABC classification.